Vaccinia virus strain LC16m8 defective in the B5R gene keeps strong protection comparable to its parental strain Lister in immunodeficient mice - Yokote, Hiroyuki; Shinmura, Yasuhiko; Kanehara, Tomomi; Maruno, Shinichi; Kuranaga, Masahiko; Matsui, Hajime; Hashizume, So (Vaccine, 2015)
Attenuated vaccinia virus strain, LC16m8, defective in the B5R envelope protein gene, is used as a stockpile smallpox vaccine strain in Japan against bioterrorism: the defect in the B5R gene mainly contributes to its highly attenuated properties. The protective activity of LC16m8 vaccine against challenge with a lethal dose of vaccinia Western Reserve strain was assessed in wild-type and immunodeficient mice lacking CD4, MHC class I, MHC class II or MHC class I and II antigens. The immunization with LC16m8 induced strong protective activity comparable to that of its parent strain, Lister (Elstree) strain, in wild-type mice from 2 days to 1 year after vaccination, as well as in immunodeficient mice at 2 or 3 weeks after vaccination. These results implicated that the defect in the B5R gene hardly affected the potential activity of LC16m8 to induce innate, cell-mediated and humoral immunity, and that LC16m8 could be effective in immunodeficient patients. LC16m8 with truncated B5 protein has an activity to induce immunity, such as innate immunity and subsequent cell-mediated and humoral immunity almost completely comparable to the activity of its parental strain Lister.